Microbiome profiling of rotavirus infected children suffering from acute gastroenteritis - Muhammad U. Sohail (9522515) (2022)
Background Rotavirus (RV) is a leading cause of pediatric diarrhea and mortality worldwide. The virus causes acute gastroenteritis characterized by moderate to severe vomiting, diarrhea, dehydration, and fever. Microbial dysbiosis caused by RV infection may significantly influence disease prognosis and the development of other chronic diseases. The gut microbiome plays a vital role in enteric immune response for rotavirus vaccine (RVV) that requires further elucidations. The current study evaluates the gut microbiome of RV positive children and compares gastroenteritis manifestation in children admitted to the Pediatric Emergency Centre, Hamad Medical Cooperation, Doha, Qatar. Stool samples were collected from thirty-nine RV positive and eight healthy control children. 16S rRNA sequence was performed using the Illumina MiSeq platform. Results The data demonstrated a significant increase in microbiome diversity denoted by higher relative abundances of phylum Proteobacteria (p = 0.031), Fusobacteria (p = 0.044) and genus Streptococcus (p ≤ 0.001) in the infected group relative to the control. Similarly, district clustering pattern (PERMANOVA p = 0.01) and higher species richness (Shannon entropy p = 0.018) were observed in the children who received two RVV doses compared with the non-vaccinated or single-dose groups. These microbiome changes were represented by over-abundance of phylum Bacteroidetes (p = 0.003) and Verrucomicrobia (p ≤ 0.001), and lower expression of family Enterobacteriaceae in two RVV doses group. However, microbiome composition was not associated with diarrhea, vomiting, and other parameters of gastroenteritis. Conclusions The observations assert significant microbial signatures of RVV, which is dose-dependent, and suggest manipulating these microbes as a novel approach for improving RVV efficacy. Further studies are warranted to investigate the immune status of these patients and mechanistic investigation to enhance RVV seroconversion. Other Information Published in: Gut Pathogens License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1186/s13099-021-00411-x